2019
DOI: 10.3390/genes11010044
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Epidemic Diarrhea Altered Colonic Microbiota Communities in Suckling Piglets

Abstract: Porcine epidemic diarrhea (PED) is a major gastrointestinal disease afflicting suckling pigs that causes huge industrial economic losses. In this study, we investigated microbiota from the colonic mucosa and content in healthy and PED piglets. High-throughput 16S rRNA gene sequencing was performed to identify inter-group differences. Firmicutes, Fusobacteria, Proteobacteria, and Bacteroidetes were the top four affected phyla. The proportion of Proteobacteria was higher in infected than in healthy piglets, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
(43 reference statements)
4
11
0
1
Order By: Relevance
“…However, several significant differences of diversity indices were observed in the jejunum, colon, and cecum, particularly the obvious clusters of beta diversity between the healthy and the PEDV-infected piglets, indicating the community of the gut microbiota was markedly altered by PEDV infection. Similar findings were obtained by Huang et al ( 16 ) and ( 17 ). Interestingly, increased alpha diversity indices (Shannon and Simpson) were observed in the PEDV-infected piglets, implying PEDV infection led to the dysbiosis of porcine microbiome.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, several significant differences of diversity indices were observed in the jejunum, colon, and cecum, particularly the obvious clusters of beta diversity between the healthy and the PEDV-infected piglets, indicating the community of the gut microbiota was markedly altered by PEDV infection. Similar findings were obtained by Huang et al ( 16 ) and ( 17 ). Interestingly, increased alpha diversity indices (Shannon and Simpson) were observed in the PEDV-infected piglets, implying PEDV infection led to the dysbiosis of porcine microbiome.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, increased alpha diversity indices (Shannon and Simpson) were observed in the PEDV-infected piglets, implying PEDV infection led to the dysbiosis of porcine microbiome. This result is similar to the finding of Huang et al ( 16 ) that alpha diversity increased with time during PEDV infection, but is contrary to results of Song et al ( 12 ) and ( 17 ). Nevertheless, Chao index in the ileum was found as the only difference between the control and NAC groups, no other variation was found between the control and NAC groups and between the PEDV and the PEDV+NAC groups, suggesting a slight effect of NAC on the bacterial community.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Huang et al observed similar effects on the dynamic change of gut microbiota in suckling piglets, with more pronounced changes occurring at later time points during the period of 1-to 3-week of age [58]. Tan et al also noted similar trends in microbial changes in the cecal mucosa and contents of suckling piglets [59]. In addition, Langel et al determined that the stage of gestation at which PEDv infection occurs in pregnant sows affects maternal immunity and lactogenic immune protection of neonatal suckling piglets [60].…”
Section: Production Phase Vulnerabilitiesmentioning
confidence: 77%